A randomised trial of 4- versus 12-weekly administration of bone-targeted agents in patients with bone metastases from breast or castration-resistant prostate cancer. (January 2021) - Clemons, Mark; Ong, Michael; Stober, Carol; Ernst, Scott; Booth, Christopher; Canil, Christina; Mates, Mihaela; Robinson, Andrew; Blanchette, Phillip; Joy, Anil Abraham; Hilton, John; Aseyev, Olexiy; et al.
Abstract: Background: Optimal dosing of bone-targeted agents (BTAs), in patients with bone metastases remains an important clinical question. This trial compared 4-weekly versus 12-weekly therapy. Patients and methods: Patients with bone metastases from breast or castration-resistant prostate cancer (CRPC), who were going to start or already on BTAs, were randomised 1:1 to 4-weekly or 12-weekly BTA treatment for one year. Primary end point was change in health-related quality of life (HRQoL)-physical function European Organisation for Research and Treatment of Cancer (EORTC)-QLQ-C30). Secondary end points included pain (EORTC-QLQ-BM22), global health status (EORTC-QLQ-C30), symptomatic skeletal events (SSEs) rates and time to SSEs. Primary analysis was per protocol and a non-inferiority margin of 5 points was used. Results: Of 263 patients (160 breast cancer, 103 CRPC), 133 (50.6%) and 130 (49.4%) were randomised to the 4- and 12-weekly groups, respectively. BTAs included denosumab (56.3%), zoledronate (24.0%) and pamidronate (19.8%). Using repeated-measures analysis, across all time points, patients in the 4-weekly arm had a mean HRQL-physical subdomain score which was 1.2 (95% confidence interval: -1.6 to 4.0) higher than the 12-weekly arm. The study met the definition of non-inferiority for our primary outcome. Secondary outcomes showed no significant difference in scores for pain, global health status, SSE rates and SSE-free survival between arms. Subgroup analyses for cancer type, prior BTA use or BTA type showed no significant difference between arms. Conclusion: These results in addition to those previously reported for de-escalating zoledronate and systematic reviews in both breast and prostate cancers, would support that de-escalation of commonly used BTAs is a reasonable treatment option. Highlights: Four- versus 12-weekly therapy of bone-targeting agents in patients with bone metastases from breast or prostate cancer. BTAs used in the study are pamidronate, zoledronate and denosumab. Twelve-weekly therapy was non-inferior to 4-weekly therapy for the primary outcome of health-related quality of life. No significant difference was seen in symptomatic skeletal event (SSE) rates and SSE-free survival between arms. Results consistent with previous studies, suggests that de-escalation of BTAs is a reasonable treatment option.